Evaluating health outcomes in the treatment of hypothyroidism - Ettleson, Matthew D.; Papaleontiou, Maria (Frontiers in Endocrinology, 2022)
Clinical hypothyroidism is defined by the inadequate production of thyroid hormone from the thyroid gland to maintain normal organ system functions. For nearly all patients with clinical hypothyroidism, lifelong treatment with thyroid hormone replacement is required. The primary goal of treatment is to provide the appropriate daily dose of thyroid hormone to restore normal thyroid function for each individual patient. In current clinical practice, normalization of thyrotropin (TSH) level is the primary measure of effectiveness of treatment, however the use of a single biomarker to define adequate thyroid hormone replacement is being reevaluated. The assessment of long-term clinical health outcomes and patient-reported outcomes (PROs), often within the context of intensity of treatment as defined by thyroid function tests (i.e., undertreatment, appropriate treatment, or overtreatment), may play a role in evaluating the effectiveness of treatment. To date, overall mortality, cardiovascular morbidity and mortality, bone health and cognitive function have been evaluated as endpoints in clinical outcomes studies in patients with treated hypothyroidism. More recent investigations have sought to establish the relationships between these end-results and thyroid function during the treatment course. In addition to clinical event outcomes, patient-reported quality of life (QoL) has also been considered in the assessment of adequacy of hypothyroidism treatment. From a health care quality perspective, treatment of hypothyroidism should be evaluated not just on its effectiveness for the individual patients but also to the extent to which patients of different sociodemographic groups are treated equally. Ultimately, more research is needed to explore differences in health outcomes between different sociodemographic groups with hypothyroidism. Future longitudinal studies of treated hypothyroidism that integrate biochemical testing, PROs, and end-result clinical outcomes could provide a more complete picture into the effectiveness of treatment of hypothyroidism.